Hydrogels for application in soils under abiotic stresses of Drylands - Nascimento, Carla Danielle Vasconcelos do (2020)
The use of superabsorbent hydrogels for application in soils has been studied once they can retain water to improve soil water availability for plant growth. However, the loss of water absorption/retention capacity of hydrogels raises doubts about their long-term efficacy, since there are evidences that abiotic factors affect their efficiency, degradation, and residual levels of acrylamide. Three laboratory studies were carried out to evaluate hydrogels under temperature and salinity stresses. In the first study, the effects of salinity on hydrogel efficiency and potential degradation were evaluated through an experiment in split plot design with four evaluation times (30, 60, 90 and 120 days), five salinity levels (0.003, 0.5; 1.5; 3.0 and 6.0 dS m-1), and four repetitions. The swelling, composition, and residual acrylamide concentration of a commercial hydrogel were evaluated. In the second study, the effect of temperatures on the physical attributes of soil amended with commercial hydrogel was evaluated through an experiment in split plot scheme with four temperatures (30; 45; 65 and 105 °C), four exposure times (40, 70, 100, and 130 days), and four repetitions. Moisture at field capacity and permanent wilting point, available water, soil density and porosity were evaluated. The third study was a factorial experimental design in a (3x4x2) scheme. The treatments were three hydrogels (A, B, and C), four temperatures (20, 30, 40, and 65 °C), and two salinities (0.003 and 3.0 dS m-1) with four replications. The swelling degree and the residual acrylamide concentration of the hydrogels were measured. Data were analyzed with univariate (for all studies) and multivariate statistics (for the third study). The first study revealed that there is a reduction in the hydrogel capacity for water absorption over time and with increasing salinity levels. Despite abiotic factors compromising water absorption by the hydrogel, in the second study beneficial effects on soil water storage capacity (up to three times increase), density (reduction of up to 15%), and porosity (up to 15% increase) were observed. Temperature tolerance of the hydrogels evaluated in the third study should be improved so they can be used in regions with high temperatures and salinity levels. Residual acrylamide levels of hydrogels decreased up to 95% over 30 days and are safe for application to soils. In general, anionic superabsorbent co- polymers have the potential to contribute to soil management under abiotic stresses typical of drylands.